Implication of Musyarakah Mutanaqisah Contract of Syariah Banking (Study of Opportunities and Risks at Bank Mu’amalat, Manado Branch) - Rahmawaty Rahmawaty (Tasharruf: Journal Economics and Business of Islam, 2019)
AbstractThe growing of Sharia Banking has also encouraged the development of its products. One of the sharia banking products that in high demand by the public is housing finance products known as the kongsi pemilikan rumah syari`ah (KPRS). In its implementation, there are differences in some sharia banks; some use the murabahah and other use musyarakah mutanaqishah contracts. In 2008, the National Sharia Council issued a fatwa regarding the musyarakah mutanaqisah contract in financing home ownership. However, the contract was still not implemented by all Sharia banking. In 2012, Bank Indonesia issued a circular letter to all Sharia Banks and Sharia Business Units which further legitimized the application of the musyarakah mutanaqisah contract in sharia banking. Contracts of Musyarakah mutanaqisah in KPR products will facilitate customers in financing the KPR. The advantages of the musyarakah mutanaqisah contract for customers are the more extended financing periods and relatively cheaper installments.Keywords: Mutaqisah Musyarakah contract, Home Ownership Financing.